Keterkaitan Pemberian Jumlah Pakan Terhadap Hasil Panen Ikan Bandeng di Desa Mekuntur Kecamatan Glagah Kabupaten Lamongan - Sa'adah, Wachidatus (Universitas Galuh, 2026)
This study aims to analyze the extent to which the amount of feed given is related to the harvest yield of milkfish (Chanos chanos) in Lamongan Regency, using a quantitative approach. The analysis was conducted using correlation and regression methods. The results of the analysis showed a correlation coefficient (r) of 0.728, indicating a strong and positive relationship between the amount of feed and the harvest yield of milkfish. The t-test with a calculated t-value of 4.25 is greater than the table t-value of 2.571 at a 5% significance level, confirming the significance of the relationship. The regression equation Y = 1.0625 + 4.75X shows that each additional unit of feed increases the average yield by 4.75 units. It can be concluded that the amount of feed has a significant effect on milkfish harvest yield, so that proper feeding is the key to increasing harvest yield and the sustainability of milkfish farming in Mekuntur Village, Glagah District, Lamongan Regency.